2009
DOI: 10.1634/theoncologist.2009-0099
|View full text |Cite
|
Sign up to set email alerts
|

Nodular Lymphocyte Predominant Hodgkin Lymphoma

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 87 publications
1
40
0
6
Order By: Relevance
“…According to a review an increased risk has been observed for secondary NHL in NLPHL patients with about 1-5% and molecular analysis of immunoglobulin heavy chain gene rearrangements indicates that some cases of the secondary NHL may share a common clonal origin with the primary NLPHL [16]. In our case, the TCRLBCL most (HE stain, 940).…”
Section: Discussionmentioning
confidence: 48%
“…According to a review an increased risk has been observed for secondary NHL in NLPHL patients with about 1-5% and molecular analysis of immunoglobulin heavy chain gene rearrangements indicates that some cases of the secondary NHL may share a common clonal origin with the primary NLPHL [16]. In our case, the TCRLBCL most (HE stain, 940).…”
Section: Discussionmentioning
confidence: 48%
“…Compared with classical HL, NLPHL shows a slightly older median age at presentation (30-40 years), greater male predominance (3:1), less mediastinal involvement (<15%), greater representation of limited stage disease (70%-80%), lower occurrence of cHL risk factors [9] and less aggressive tumor growth [22,23]. When diagnosed and treated in early favorable stages, NLPHL is associated with an excellent prognosis [19], with response rates to primary therapy exceeding 90% [9] and complete remission (CR) rates exceeding 95% [10].…”
Section: Discussionmentioning
confidence: 97%
“…When diagnosed and treated in early favorable stages, NLPHL is associated with an excellent prognosis [19], with response rates to primary therapy exceeding 90% [9] and complete remission (CR) rates exceeding 95% [10]. However, progression to DLBCL-like lesions has been reported in approximately 3-5% of cases [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations